2013
DOI: 10.1074/jbc.m113.494591
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CD47 Impairs Bone Cell Differentiation and Results in an Osteopenic Phenotype in Vivo due to Impaired Signal Regulatory Protein α (SIRPα) Signaling

Abstract: Background: CD47 and its receptor SIRP␣ are suggested to regulate bone metabolism. Results: Lack of CD47 prevents stromal cell SIRP␣ signaling, which impairs bone marrow stromal cell differentiation, subsequent osteoclast differentiation, and bone homeostasis. Conclusion: CD47 and SIRP␣ both mediate normal bone cell and bone tissue formation. Significance: CD47/SIRP␣ may be a future molecular target to modulate bone homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…TSP1‐CD47 interactions play a role in the formation of multiple myeloma‐dendritic cell fusions with bone‐resorbing capacity, and TSP1‐CD36 ligation can promote osteoclastic resorption on dentine slices . CD47−/− mice have a bone resorption defect, which we have shown is due to increased iNOS in OCs . Together these data led us to hypothesize that OB‐secreted TSP1 sequestered in bone matrix will modulate OC function thereby coupling OB activity to OC formation.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…TSP1‐CD47 interactions play a role in the formation of multiple myeloma‐dendritic cell fusions with bone‐resorbing capacity, and TSP1‐CD36 ligation can promote osteoclastic resorption on dentine slices . CD47−/− mice have a bone resorption defect, which we have shown is due to increased iNOS in OCs . Together these data led us to hypothesize that OB‐secreted TSP1 sequestered in bone matrix will modulate OC function thereby coupling OB activity to OC formation.…”
Section: Introductionmentioning
confidence: 63%
“…TSP1 is expressed by OBs and is present in osteoid and mineralized bone matrix, where it is directly deposited by bone‐forming OBs . TSP1 is involved in OB differentiation in part through activation of latent TGF‐β, and TSP1 receptors CD47 and CD36 also regulate OB . TSP1 is a regulator of NO in endothelial cells, platelets, and vascular smooth muscle cells, but only receptors CD36 and CD47 have been implicated in NO regulation .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the total number of OCs with three nuclei or more was analyzed at the end of the culture, but without reporting details on the actual number of nuclei per cell (Lundberg et al, 2007; Maile et al, 2011; Koskinen et al, 2013). In our recent study (Hobolt‐Pedersen et al, 2014), we used a CD47 blocking‐antibody and evaluated at the end of the culture the number of nuclei in all OCs both in control condition as well as in the presence of the blocking antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent of these is DC‐STAMP (dendritic cell‐specific transmembrane protein) (Kukita et al, 2004; Yagi et al, 2005; Iwasaki et al, 2008; Mensah et al, 2010; Chiu et al, 2012; Chiu and Ritchlin, 2016), which has been identified as one of the most essential single factors supporting both differentiation and fusion. However, also other factors such as CD47 (Han et al, 2000; Lundberg et al, 2007; Maile et al, 2011; Koskinen et al, 2013; Hobolt‐Pedersen et al, 2014), syncytin‐1 (Soe et al, 2011), OC‐STAMP (osteoclast stimulatory transmembrane protein) (Miyamoto et al, 2012; Witwicka et al, 2015), dynamin (Shin et al, 2014; Verma et al, 2014), Pin1 (peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1) (Islam et al, 2014; Cho et al, 2015), and e‐cadherin (Mbalaviele et al, 1995; Fiorino and Harrison, 2016) are involved in OC fusion, but it is important to stress that this list is not exhaustive. In order to identify the role of these factors , a series of molecular techniques, and cellular model systems have been employed, which in general are evaluated through end‐point measurements by counting the number of multi‐nucleated OCs, number of nuclei per OC, resorptive activity, and so forth at the end of the incubation period.…”
mentioning
confidence: 99%
“…Blocking antibodies against CD47 and SIRPα also reduced the numbers of TRAP + osteoclasts formed in cultures of murine hematopoietic cells stimulated by M-CSF and RANKL. Further study identified reduced expression of the osteoclastogenic genes nfatc1 , Oscar , Trap/Acp , ctr , catK , and dc-stamp in bone marrow cultures from cd47 −/− mice stimulated with parathyroid hormone or 1α,25(OH) 2 -vitamin D3 (Koskinen et al, 2013). Stromal cells lacking either CD47 or the cytoplasmic tail of SIRPα were defective in supporting osteoclastogenesis in WT bone marrow-derived macrophages.…”
Section: Tsp1-cd47-sirpα Regulation In Bone Developmentmentioning
confidence: 99%